2020
DOI: 10.1038/s41598-020-57501-0
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish C-reactive protein isoforms inhibit SVCV replication by blocking autophagy through interactions with cell membrane cholesterol

Abstract: Phosphorylcholine works not only as a pathogen-associated molecular pattern (PAMP) 10,18-20 , but also as a danger-associated molecular pattern (DAMP) 18,21-24. This phosphorylcholine-binding site of the soluble CRP is also involved in interactions with, for instance, oxidized low-density lipoprotein (LDL) 21 , nuclear materials (such as chromatin, histones, small nuclear ribonucleoproteins) 25,26 , and other compounds that may not contain phosphorylcholine but are abundant in bacteria 27 , fungi 28,29 and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 99 publications
3
22
0
Order By: Relevance
“…Glycerophospholipid metabolism is involved in the biosynthesis of PC and PE. An increasing number of studies have shown that disorders of glycerophospholipid metabolism in cells can lead to onset of diseases ( Bello-Perez et al, 2020 ; Wang et al, 2020 ). In this study, the metabolism of glycerophospholipids, especiallyPC(38:2) and PE(36:1) were found to be the most enriched pathway during BmCPV infection, indicating that glycerophospholipid metabolism may be crucial for the pathogenesis of BmCPV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycerophospholipid metabolism is involved in the biosynthesis of PC and PE. An increasing number of studies have shown that disorders of glycerophospholipid metabolism in cells can lead to onset of diseases ( Bello-Perez et al, 2020 ; Wang et al, 2020 ). In this study, the metabolism of glycerophospholipids, especiallyPC(38:2) and PE(36:1) were found to be the most enriched pathway during BmCPV infection, indicating that glycerophospholipid metabolism may be crucial for the pathogenesis of BmCPV.…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein A-I binding protein is an intrinsic factor that suppresses human immunodeficiency virus (HIV) replication ( Dubrovsky et al, 2020 ). Zebrafish C-reactive protein-like protein inhibits spring viraemia of carp rhabdovirus replication by causing alterations of cholesterol ratios in the host cellular membranes ( Bello-Perez et al, 2020 ). Lipids have also been shown to play important roles in the replication of coxsackievirus B3 ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…PCR analysis was amplified as follows: 95 °C for 30 s, denaturation for 40 cycles at 95 °C for 15 s, and annealing at 60 °C for 60 s. To assess the specificity of each amplicon, melt curve analysis was also performed at the end of each thermal profile. The sequences of primers are listed in Table 1 ( Bello-Perez et al, 2020 ; Gotesman et al, 2015 ; Varela et al, 2014 ). Each sample was run in triplicate and the β-actin gene was used as an internal control for normalization.…”
Section: Methodsmentioning
confidence: 99%
“…Recent observations have suggested that the anti‐SVCV activity mediated by zebrafish Crp proteins is related to their ability to inhibit the autophagic process (Belló‐Pérez et al . 2020), a mechanism that is known to be essential for SVCV replication (Liu et al . 2015).…”
Section: Fish and Non‐piscine Immune Proteinsmentioning
confidence: 99%